Pengaruh Sistem Pembelajaran Pesantren Kampus terhadap Penguatan Akidah dan Akhlak Mahasiswa IAIN Samarinda - Nursiyam, Nursiyam (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2015)
Learning system is a unity component that has connection each other to achieve the purpose wanted. But the focus of learning systems in this research is about theology and morals that has been submitted is not only to understood but also must be able to practiced. The purpose of this research to knows effect of boarding campus learning system to the strengthening of theology and morals college student of IAIN Samarinda. This research is a descriptive research with a quantitative approach. The population in this research is all college students of boarding campus IAIN Samarinda the academic year 2014/2015 that lives in dormitory with a number of 230 college campus. The sample in this research is 10% or 23 college student who is selected by simple random sampling technique. The data collection techniques using questionnaires, observation, documentation, and interviews while data analysis techniques using the formula mean and multiple coefficient correlation product moment. The research results is known that the learning system of boarding campus, theology, and morals college students is calculated by the formula mean equally good, because it is in the same interpretation of mean is located in 3.410 - 4.200. In the analysis of multiple coefficient correlation product moment the value is gotten 0.454, and the hypothesis is accepted because the calculated value multiple coefficient correlation product moment greater than the value of r table is 0.454 > 0.413. As well as the formula multiple coefficient correlation product moment if 0.454 is interpreted that value lies in the 0.400 - 0.599 is considered influential enough. So the research results is there are influence of boarding campus learning system the strengthening of theology and morals IAIN students Samarinda. Based on the results obtained, the researchers recommend that boarding campus should increase religious learning system, especially dormitory increase the rules, and the college students should be able to pay attention and obey the rules of learning campus pesantren (boarding) well.